Effect of Maternal Distress on Perceptions of Infant Behavior May Differ in Chinese-American and European-American Mothers and Infants. Issue 3 (April 2020) - Liu, Cindy H.; Snidman, Nancy; Kagan, Jerome; Tronick, Ed
ABSTRACT: Objective: This study examined the associations between maternal distress (symptoms of depression and anxiety) and observer and maternal ratings of infant temperament in Chinese-American (CA) and European-American (EA) 4-month-old infants ( N = 114 dyads). Methods: Maternal distress was obtained through self-reported symptoms of depression and anxiety. Mothers reported infant temperament (distress at limitations, soothability, and fear) through the short form of the Infant Behavior Questionnaire—Revised. To obtain observer-rated infant reactivity, infants were administered a battery of visual and auditory stimuli in the laboratory, in which infant behaviors (fret/cry, limb activity, and arching of the back) were coded. Results: Maternal distress accounted more for the maternal perception of her infant among EA mothers than among CA mothers, but the relation was only observed for soothability. Higher maternal distress was associated with maternal report of lower soothability for EA mothers. Observer-rated infant reactivity, but not maternal distress, was positively associated with EA and CA maternal report of distress at limitations. Observer-rated infant negativity was associated with somewhat higher ratings of infant fear for EA mothers, although this association for EA mothers was not significantly different from CA mothers. Conclusions: Potential biases in maternal report of infant behavior due to effects from maternal distress may not be generalizable across cultures but may vary because of cultural norms for emotional experience and expectations for infant behavior. EA mothers' ratings of infant distress and soothability, but not fear, may be influenced by maternal distress.